(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Solid self-emulsifying delivery system containing pitavastatin calcium was developed using oil and hydrophilic surfactants. Pitavastatin calcium has low solubility and low bioavailability; hence, it was meaningful to improve solubility and dissolution properties by using suitable formulation component and process. Based on preliminary study, oleic acid, Tween 20 and PEG 400 were utilized for development of self-emulsifying system. Microemulsion region was identified by pseudo-ternary phase diagrams. The liquid system: adsorbent (Aerosil 200) at a ratio of 2:1 was employed for spray drying. The system was evaluated for emulsification time, percent drug content, in-vitro dissolution. The other analytical techniques used for characterization were fourier transform infrared spectroscopy (FTIR), DSC, standard error of the mean (SEM), particle size, zeta potential and XRD. The optimized formulation had particle size of 172.2 nm and the drug content found was 96.38%. It also had shown 95.98% drug release at the end of 1 hr which was more when compared to pure drug. It was observed that increase in surfactant concentration decreases dispersion time and particle size with concomitant increase in amount of drug released. The XRD diffractogram confirmed the conversion of drug from crystalline to amorphous form. The spray dried particles had smoother surface. The DSC thermogram showed no melting endotherm in the system indicating well dispersed drug with amorphous nature.